1984
DOI: 10.1007/bf00495433
|View full text |Cite
|
Sign up to set email alerts
|

Wheat-germ agglutinin binding in four types of mouse peritoneal macrophage

Abstract: After stimulation of the mouse peritoneal cavity with newborn calf serum (NBCS), four types of monocyte and macrophage were distinguished on the basis of peroxidase (PO) patterns. These cell types showed heterogeneity in their binding of the lectin wheat-germ agglutinin (WGA). At 16 h after stimulation, monocytes and monocyte-derived macrophages (with PO activity in granules) had a high level of WGA binding; PO-negative macrophages showed moderate WGA binding, and resident macrophages (with PO activity in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

1985
1985
1993
1993

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 18 publications
3
3
0
Order By: Relevance
“…These cells subsequently acquired PO activity in the RER and NE. The assumption that PO-negative macrophages are precursor cells of resident macrophages is in line with previous data, from which it could be deduced that the PO-negative macrophages are related to resident macrophages [9][10][11][12]17). An interesting question, then, is whether these PO-negative macrophages are monocytederived.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…These cells subsequently acquired PO activity in the RER and NE. The assumption that PO-negative macrophages are precursor cells of resident macrophages is in line with previous data, from which it could be deduced that the PO-negative macrophages are related to resident macrophages [9][10][11][12]17). An interesting question, then, is whether these PO-negative macrophages are monocytederived.…”
Section: Discussionsupporting
confidence: 81%
“…Thus, the expression of WGA binding sites seems to diminish during the differentia tion of promonocytes to exudate macrophages. This assumption is supported by results of a previous study, which showed that blood monocytes express more WGA binding sites than monocytes and macrophages from the peritoneal cavity and that peritoneal exudate macrophages lose WGA binding sites with increasing time after intraperitoneal injection of a stimulus [12]. Under the latter experimental conditions,…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…The specimens were incubated in 0-1 M cacodylate buffer (pH 7.4) with 0-5 mg m1-1 3,3'-diaminobenzidine (DAB, Sigma) and 0.01% H202 for 4 h at 37°C to demonstrate peroxidase activity of the neutrophils [4]. For examination of catalase activity, the samples were incubated in 2 mg ml -~ DAB and 0.03% H202 in 0.05 M propandiol buffer (pH 9.5) for 4 h at 37°C.…”
Section: Cytochemical Electron Microscopymentioning
confidence: 99%